Unifying concept of pelvic floor disorders and incontinence. - Swash, M (1985)
Denervation of pelvic floor sphincter muscles is a feature of pelvic floor disorders. When severe, it may be accompanied by stress incontinence of faeces, or of urine. The extent of chronic partial denervation of these pelvic floor muscles can be quantified by electromyography (EMG), and its cause identified by electrophysiological studies of the motor innervation of these striated muscles. Damage to this innervation is often initiated by childbirth, but appears to progress during a period of many years so that the functional disorder usually presents in middle life. Incontinence develops in some patients, but not in others. This can be predicted by the severity of the abnormalities found in EMG studies of the pelvic sphincter musculature and motor latency studies of its innervation. The results of such investigations in the six common types of pelvic floor disorder are presented. Recognition of the causative factors leading to damage to the innervation of the pelvic sphincter muscles implies new approaches to treatment and to prevention of pelvic floor disorders and incontinence.